Design Anthropological Filmmaking for Automated Futures. (September 2022) - Pink, Sarah
In this article I introduce the theory and practice of Design Anthropological Filmmaking as a mode of actively proposing alternative possibilities to the technological solutionist narratives and imaginaries that dominate industry, government and policy narratives about automated futures. I argue for documentary practice that is theoretically and critically aligned with a vision of the world as ongoingly emergent, and unfinished, and contests conventional innovation paradigms. To demonstrate this theory-practice dialogue I draw on my collaborative documentaries Laundry Lives and Smart Homes for Seniors which explore everyday life in the home with digital, emerging and automated technologies.